Obtención de esencias mediante la destilación por arrastre de vapor en principales plantas aromáticas de la provincia de El Oro. - Apolo Toro, Cesar A. (2008)
Due to the growing peak of the implementation of the natural medicine or alternative in ours means to calm the aliments decided to work in the field of the essential oils, to be a wide and interesting topic and that at the present time it is investigation matter.